Gender equality in Science, Technology, Engineering and Mathematics in Taraba State, Nigeria - John Tyavbee Ajai; Chia Igbalagh Azuaga (Jurnal VARIDIKA, 2022)
Long acknowledged as the foundation for a country's growth and prosperity are four disciplines- science, technology, engineering, and mathematics (STEM).  Education in these four fields has several advantages for women in terms of long-term social and economic advancement. By 2030, the fifth sustainable development target (SDG 5) is to enable women and girls to realise their full potential. One of the criteria to determine SDG 5 is measuring gender equality in science, technology, engineering, and mathematics (STEM). In Taraba State, Nigeria, this study looks into gender equality in STEM fields. The study sample consists of 14,548 STEM-majoring students from 100 secondary schools and 6 post-secondary institutions in Taraba State, with 8,354 male and 6,194 female participants. Data on enrollment in STEM-related courses as well as information from a standardised survey were collected.The findings show that enrollment data at the secondary school level is equal for both sexes. Nonetheless, more male students chose chemistry and physics, while more female students chose biology and technical drawing. According to the tertiary institutions' findings, men predominate in STEM fields. The study comes to the conclusion that there is significant gender inequality in STEM education in Taraba State, Nigeria, and suggests that efforts should be taken to bridge the gap in order to meet SDG 5.